2020
DOI: 10.2147/cmar.s187203
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of chemoembolization with CalliSpheres® microspheres and conventional chemoembolization in the treatment of hepatocellular carcinoma: a multicenter retrospective study</p>

Abstract: This study aimed to compare the efficacy and safety between transarterial chemoembolization (TACE) with CalliSpheres ® microspheres (CSM-TACE) and conventional TACE (cTACE) in patients with hepatocellular carcinoma (HCC). Patients and Methods: Three hundred and thirty-five HCC patients receiving CSM-TACE or cTACE were consecutively enrolled in this multi-center, retrospective cohort study, and then divided into CSM-TACE group and cTACE group accordingly. Complete response (CR), objective response (ORR) and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…In the present meta-analysis, we initially searched formally published studies to comprehensively compare the efficacy and safety of CSM-TACE with that of cTACE for treating HCC patients. A total of 16 studies and 1,454 patients with HCC were included, of whom 722 were treated with CSM-TACE and 732 were treated with cTACE (14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). CR, ORR, DCR, PFS, OS, adverse events and liver function indexes were compared and analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present meta-analysis, we initially searched formally published studies to comprehensively compare the efficacy and safety of CSM-TACE with that of cTACE for treating HCC patients. A total of 16 studies and 1,454 patients with HCC were included, of whom 722 were treated with CSM-TACE and 732 were treated with cTACE (14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). CR, ORR, DCR, PFS, OS, adverse events and liver function indexes were compared and analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, only four included studies provided PFS and OS data. Three of them demonstrated a non-significant trend in favor of the CSM-TACE group, which was likely to be explained by the fact that the relative short median follow-up durations (range: 9.9-11.4 months) might reduce the statistic power (16,19,21). In contrast, another study revealed that CSM-TACE improved PFS and OS compared with cTACE in HCC patients with statistical significance (20).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment response was evaluated at 4–6 weeks after the DEB-TACE or cTACE referring to the modified Response Evaluation Criteria in Solid Tumors (mRECIST), 19 which was classified as complete response (CR), partial response (PR), stable disease (SD) and progressive disease (PD). Besides, the objective response rate (ORR) was calculated as the sum of CR and PR, and the disease control rate (DCR) was calculated as the sum of CR, PR, and SD.…”
Section: Methodsmentioning
confidence: 99%
“…Most HCC patients are typically diagnosed at intermediate or advanced stages when curative treatments cannot be applied [ 71 , 72 ]. According to the Barcelona Clinic Liver Cancer (BCLC) staging system [ 73 ] and several treatment guidelines [ 6 , 7 ], TACE is the gold standard for patients with intermediate-stage HCC.…”
Section: Methodsmentioning
confidence: 99%